2016
DOI: 10.1103/physrevd.93.114514
|View full text |Cite
|
Sign up to set email alerts
|

Strongly interacting dynamics and the search for new physics at the LHC

Abstract: We present results for the spectrum of a strongly interacting SU(3) gauge theory with $N_f = 8$ light fermions in the fundamental representation. Carrying out non-perturbative lattice calculations at the lightest masses and largest volumes considered to date, we confirm the existence of a remarkably light singlet scalar particle. We explore the rich resonance spectrum of the 8-flavor theory in the context of the search for new physics beyond the standard model at the Large Hadron Collider (LHC). Connecting our… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
180
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(189 citation statements)
references
References 55 publications
9
180
0
Order By: Relevance
“…The masses M π and M d can be found by measuring the exponential fall of appropriate correlation functions, and F π can be extracted from simulations of the axial-vector current correlator. It is defined using the same conventions as in [15]. The extraction of F d from a lattice measurement of a correlation function in the underlying gauge theory has not yet been reported.…”
Section: Jhep07(2017)035mentioning
confidence: 99%
See 2 more Smart Citations
“…The masses M π and M d can be found by measuring the exponential fall of appropriate correlation functions, and F π can be extracted from simulations of the axial-vector current correlator. It is defined using the same conventions as in [15]. The extraction of F d from a lattice measurement of a correlation function in the underlying gauge theory has not yet been reported.…”
Section: Jhep07(2017)035mentioning
confidence: 99%
“…This is consistent with the estimate of finite-volume and lattice-discretization artifacts reported in ref. [15]. In addition, there are systematic uncertainties associated with the EFT we employ.…”
Section: Application To the Lsd Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In view of this it is especially interesting that lattice studies of near-conformal strong gauge theories report evidence of a scalar state that is significantly lighter than what occurs in QCD-like theories. Three groups [1][2][3][4][5] find that an SU(3) gauge theory with a sufficient number of light fermions generates a light singlet scalar state with a mass similar to the mass of the pseudoscalar state over the range of explicit fermion masses that have been studied. These groups also claim that this occurs in a phase with dynamical chiral symmetry breaking.…”
Section: B Numerics 12mentioning
confidence: 99%
“…Except for relating F π to the vacuum expectation value (vev) of the SM, there is no free parameter in our model resulting in high predictivity. Of special interest is the iso-singlet scalar (0 ++ ) meson because in dilaton-like scenarios it is the candidate for the Higgs boson and numerical investigations of conformal or near-conformal theories have found that it is much lighter than the vector resonance, often degenerate or even below the pseudoscalar [11,14,[17][18][19][20]. Determining the mass of the iso-singlet scalar is challenging because the iso-singlet scalar has the same quantum numbers as the vacuum.…”
Section: The Four Plus Eight Model and The Iso-singlet Scalarmentioning
confidence: 99%